The endolysosomal cysteine cathepsins L and K are involved in macrophage‐mediated clearance of Staphylococcus aureus and the concomitant cytokine induction. Issue 1 (13th September 2013) - Müller, Sabrina; Faulhaber, Anja; Sieber, Carolin; Pfeifer, Dietmar; Hochberg, Tanja; Gansz, Martina; Deshmukh, Sachin D.; Dauth, Stephanie; Brix, Klaudia; Saftig, Paul; Peters, Christoph; Henneke, Philipp; et al.
Abstract : Cysteine cathepsins are endolysosomal cysteine proteases highly expressed in macrophages; however, their individual contributions to the elimination of bacteria and bacteria‐induced cytokine production by macrophages are unknown. We assessed the contribution of cysteine cathepsins to macrophage defense pathways against Staphylococcus aureus by using chemical inhibitors and by infecting primary bone marrow–derived macrophages deficient in 1 of 7 major macrophage‐expressed endolysosomal cysteine proteases. We show that cysteine cathepsins are involved in the phagocytosis and killing of S. aureus . Cathepsin L was identified as an executor of nonoxidative killing. Moreover, microarray data revealed cysteine cathepsins to be important for the maximal induction of certain proinflammatory genes, such as IL6, in response to S. aureus . Cysteine cathepsin's contribution to IL6 production was dependent on phagocytosis, and cathepsin K was identified to be a critical protease in this process. Analysis of macrophages with impaired trafficking of endolysosomal Toll‐like receptors (TLRs) to the acidic compartment revealed that they were not involved in cathepsin‐dependent IL6 induction. Because IL6 production was completely dependent on the TLR‐adaptor protein myeloid differentiation primary response gene 88 (MyD88), it appears that other TLRs are involved. In summary, lysosomal cysteine proteases are functionally linked to the complex bactericidal and inflammatory activities of macrophages.—Müller, S., Faulhaber, A., Sieber, C., Pfeifer, D., Hochberg, T., Gansz, M., Deshmukh, S. D., Dauth, S., Brix, K., Saftig, P., Peters, C., Henneke, P., Reinheckel, T. The endolysosomal cysteine cathepsins L and K are involved in macrophage‐mediated clearance of Staphylococcus aureus and the concomitant cytokine induction. FASEB J . 28, 162–175 (2014). www.fasebj.org